Unidirectional plasmonically induced transparency behavior in a compact graphene-based waveguide. (3rd July 2017) - Zhang, Zhengren; Long, Yang; Zang, Xiaofei
Abstract: A graphene-based waveguide structure is proposed to achieve a unidirectional plasmonically induced transparency (PIT) behavior. In this structure, a standing-wave cavity can be formed in the graphene waveguide by controlling the Fermi energy at a different part of the graphene. Two resonant graphene ribbons are placed at the node and antinode of the standing-wave cavity field, respectively. Its corresponding optical response coming from different incident sides show a unidirectional PIT behavior. This is because the excited bright resonant graphene ribbon located at antinode inhibits the field strength on its downstream side and causes the field redistribution on its upstream side. When the wave propagates along the sequence node-antinode, the redistribution field will excite the dark resonant graphene ribbon, such that both ribbons couple coherently and the PIT behavior appears. In contrast, when the wave propagates along the sequence antinode-node, the dark resonant graphene ribbon remains dark, and no PIT appears. Our results may benefit novel nonreciprocal devices in the future.